SISTEM PENCARIAN LONTAR BERBASIS WEB DENGAN METODE VECTOR SPACE MODEL PADA DINAS KEBUDAYAAN PROVINSI BALI - Yuda Setiadi, I Kadek; Sudarma, Made; Care Khrisne, Duman (Jurnal SPEKTRUM; Vol 5 No 2 (2018): Jurnal SPEKTRUM, 2018)
This study aims to assist in the search for lontar images with Information Retrieval System built using the Vector Space Model method. The search system testing resulted in a lontar search system that received recall values: 75.4% and precision: 100% based on the graph of the receiver operating characteristic (ROC) analysis. Testing with System Usability Scale (SUS) tested at the Bali Provincial Culture Office got the highest score on statement point 1, 5 and 7 which reached 42.